The importance of growing pomegranate and ways to increase its productivity - Irgashev Abbos Djumanazarovich, (THE INNOVATION ECONOMY, 2026)
features and importance of pomegranate cultivation in this article, as well as a new environmentally friendly, resource-efficient method of pomegranate cultivation, Agrotechnology of growing medicinal pomegranate on dexqan and Farms, cultivation of the medicinal pomegranate Variety on the basis of new technology, cultivation of the medicinal pomegranate variety in Uzbekistan in the entire seasons of the year, the fact that it is possible to grow at home, on honadons – on balconies in canvases, in special crevices and greenhouses, in open areas from early bokhor in ham. The peculiarities and significance of the processing of pomegranate fruit juice, processing and the use of pomegranate plant root, body, bark on the body, glue on the body, branch, branch, leaf, flower, hawthorn, fruit, fruit from the peel and seeds are illuminated